Effect of perioperative steroids application on dysphagia, fusion rate, and visual analogue scale (VAS) following anterior cervical spine surgery: A meta-analysis of 14 randomized controlled trials (RCTs) - Zhang, Xiang; Yang, Yi; Shen, Yi-Wei; Zhang, Ke-Rui; Ma, Li-Tai; Liu, Hao (Frontiers in Surgery, 2022)
Objective: To conduct a high-level meta-analysis of the RCTs to evaluate perioperative steroids use in the management of fusion rate, dysphagia, and VAS following anterior cervical spine surgery for up to 1 year. Methods: We searched the database PubMed, EMBASE, Web of Science, Cochrane Library, Google Scholar, Ovid, and ClinicalTrials.gov without time restriction to identify RCTs that evaluate the effectiveness of perioperative steroids after anterior cervical spine surgery. A subgroup analysis was undertaken to investigate the effects of intravenous and local steroids. This study was registered in the PROSPERO database prior to initiation (CRD42022313444). Results: A total of 14 RCTs were eligible for final inclusion. This meta-analysis showed that steroids could achieve lower dysphagia rate (p＜0.001), severe dysphagia rate within one year (p＜0.001), lower VAS scores at both 1 day (p=0.005), 2 weeks (p＜0.001) and shorter hospital stay (p=0.014). However, there was no significant difference between the two groups regarding operation time (p=0.670), fusion rates (p=0.678), VAS scores at 6 months (p=0.104) and 1 year (p=0.062). There was no significant difference between intravenous and local steroid administration regarding dysphagia rates (P=0.82), fusion rate (P=1.00), and operative time (P=0.10). Conclusion: Steroids intravenously or locally following anterior cervical spine surgery can reduce incidence and severity of dysphagia within one year, VAS score within two weeks, and shorten the length of hospital stay without affecting fusion rates, increasing the operating time, VAS score at 6 months and 1 year.